MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK MENGGUNAKAN LKPD CERITA BERGAMBAR PADA MATERI PECAHAN KELAS II SEKOLAH DASAR - Rohman, Fatkhur; Murni, Cahya Intan; Utami, Pricilia Deyalita; Sholihah , Ana Putri; Nurhanurawati, Nurhanurawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Fractional learning resources in the classroom are not yet available, therefore this research was conducted. The aim of this project is to create appropriate pictorial narrative media to illustrate how children's creative thinking skills develop when used for fractional learning in grade II of primary school. Twenty students took part in the research trial stage, while twenty-one students of SD Xaverius 3 Bandar Lampung took part in the implementation stage of the 2023–2024 school year. The image narrative media produced by this study meets the criteria of validity, usefulness, and efficacy. During the testing phase, there was an 80% increase in students' creative thinking capacity and an 85% classical learning completion rate. Students' creative thinking capacity increased to 85% at the implementation stage, while the level of classical learning completeness reached 88.89%. As a result, this visual narrative medium can serve as a useful substitute for teaching students how to think creatively and understand the concept of fractions.